Frecuencia de helmintos gastrointestinales en roedores sinantrópicos capturados en el Zoológico de Barranquilla - Romero Herrera, Johan; Henao Montoya, Lina; Guimarães Riva, Henrique; Jaimes Dueñez, Jeiczon Elim (2020)
Objective: the aim of this work was to determine the prevalence and characterization of gastrointestinal parasites in synanthropic rodents at the Barranquilla Zoo. Methodology: the rodents were captured in 55 sampling locations with Tomahawk traps using non-toxic baits. Gastrointestinal parasites were evaluated through direct examination, flotation, and sedimentation. Results: Among 34 rodents (Rattus rattus) captured, 82.4% (28/34) were positive for endoparasites. Nematodes (31/49) were the most common parasite, followed by protozoa (10/49) and cestodes (8/49). Regarding nematodes, Strongylidae (24/31) was the most frequently family found, followed by Ascarididae (4/31), Ancylostomatidae (1/31), Oxyuridae (1/31) and Trichostrongylidae (1/31); for protozoa were Eimeriidae (6/10) and Entamoebidae (4/10), while for cestodes was the Hymenolepididae (8/8) family. Conclusion: R. rattus was the only species of synanthropic rat found at the Barranquilla Zoo, with the ability to be infect with several species of gastrointestinal parasites, which represent a risk of infection towards animals and humans. Objetivo: el objetivo del presente trabajo fue determinar la prevalencia y caracterización de parásitos gastrointestinales en roedores sinantrópicos que habitan en el Zoológico de Barranquilla. Metodología: para la captura de los roedores se establecieron un total de 55 puntos de muestreo en los cuales se utilizaron trampas Tomahawk con ayuda de cebos no tóxicos. Las técnicas realizadas para el diagnóstico e identificación de parásitos gastrointestinales fueron el examen directo, flotación y sedimentación. Resultados: un total de 34 roedores (Rattus rattus) fueron capturados durante el período de estudio, en los cuales la prevalencia de infección fue del 82.4% (28/34). Dentro de los diagnósticos realizados en los animales positivos, los parásitos encontrados con mayor frecuencia fueron los nematodos (31/49), seguido de los protozoos (10/49) y cestodos (8/49), respectivamente. Dentro de los nematodos, la familia ...